1999
DOI: 10.1094/phyto.1999.89.9.796
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Diaporthe phaseolorum and Phomopsis longicolla from Soybean Seeds

Abstract: Species-specific detection of Diaporthe phaseolorum and Phomopsis longicolla from soybean seeds was accomplished using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and TaqMan chemistry. To use these detection systems, fungal DNA was released from soybean seed coats using an ultrasonic processor to break the cells. DNA fragment lengths ranged from 200 to 1,200 base pairs (bp), with the majority of fragments <500 bp. Based on DNA sequences of the internal transcribed spacer (ITS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 33 publications
0
79
0
Order By: Relevance
“…caulivora. Zhang et al (1998) also by using PCRrestriction fragment length polymorphism, detected genomic differences among D. phaseolorum var. caulivora isolates and D. phaseolorum var.…”
Section: Resultsmentioning
confidence: 99%
“…caulivora. Zhang et al (1998) also by using PCRrestriction fragment length polymorphism, detected genomic differences among D. phaseolorum var. caulivora isolates and D. phaseolorum var.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the pathogenicity tests, each isolate of P. longicolla was examined for sporulation, dimension of conidia, pattern of stroma, and presence or absence of hyaline, filiform, and hamate beta conidia and perithecia to confirm identification (Hartman et al, 1999). The identifications of soybean isolates were verified previously by sequence analysis of the ITS regions and the mitochondrial small subunit rRNA genes (Li et al, 2001;Zhang et al, 1998). The identities of 11 other Phomopsis spp.…”
Section: Aggressiveness Of Phomopsis Longicolla and Other Phomopsis Smentioning
confidence: 87%
“…These primers could be used to specifically distinguish PSD-causal pathogens from each other and from other soybean fungal pathogens (Zhang et al, 1997). There were no differences in ITS sequences among seven geographically diverse isolates of P. longicolla (Zhang et al, 1998). Results from analysis of DNA from the Diaporthe -Phomopsis complex using PCR-restriction fragment length polymorphisms (PCR-RFLP) and DNA sequencing in the ITS and the 5.8 ribosomal DNA, along with morphological examination, indicated that P. longicolla is a distinct species, that D. phaseolorum var.…”
Section: Molecular Detection and Identification Of The Pathogensmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the rapid development of new molecular techniques, combined with the increasing knowledge on structure and function of resistance genes, will help getting new molecular markers for MAS (Hulbert et al 2001). Such methods offer the advantage of reducing or eliminating the need for lengthy culturing and difficult morphological identification procedures (Hamelin et al 1993;Zhang et al 1999). The potential benefits of this technology have been especially recognized in the regulatory field, where time and accuracy of identifications are crucial (Goodwin and Annis 1991;Smith et al 1996).…”
Section: Discussionmentioning
confidence: 99%